RANCANGAN KURIKULUM PROTOTYPE PEMBELAJARAN BAHASA ARAB BERORIENTASI DI MA MUHAMMADIYAH CURUP - Zulfadli Al Azimi; Muhammad Nuruzzaman Syam; Amila Sholiha (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2023)
Curriculum standards that must be the same and a complicated assessment process make the school curriculum only theoretical. Actually, what schools need is a curriculum design that is applicable to use, especially in today's digital era. Through qualitative research methods, this study aims to describe a flexible and effective curriculum design in accordance with the scope, characteristics and competencies of students. The data were obtained by means of interviews, observations, and documentation studies at MA Muhammadiyah Curup. The results of this study state that the prototype curriculum design for learning Arabic is better oriented because it fits the needs of students.